Franchising in The Form of Partnership - Kristianto, Fennieka; Gracia, Fidela (UI Scholars Hub, 2022)
The rapid advancement of business competition nowadays encouraged business actors to enhance and strengthen their networking. One of the approaches taken by business actors was to engage themselves within the franchising business. However, within this case, several issues arose, namely relating to the expansion of the business conducted by the franchisor through a partnership by way of establishing a Limited Liability Company (“LLC”) with the franchisee, particularly, concerning the management of the business. On one hand, the franchisor is acting as the owner, founder, and holder of intellectual property rights. Supplementary to that, the franchisor is likewise the major shareholder of the LLC and the franchisee is the common shareholder. Normative legal research is imposed within this research with the primary objective of examining the potential conflict of interest that may likely arise between the franchisor and the franchisee for having the form of partnership. Moreover, inequality within the franchising business relationship will likely occur since the franchisor has a larger capacity within this relationship compared to the franchisee and the possibility for the franchisee to obtain adequate protection from the agreement pertaining to the termination of the franchise agreement is considerably low.